THE RELATIONSHIP OF TEACHERS’ PERCEPTION TOWARDS LEADERSHIP CAPACITY AND ORGANIZATIONAL CULTURE IN THE MARIANISTS SCHOOLS, INDIA - Kujur, Prakash; Ye, Yan (Scholar: Human Sciences, 2018)
The main purpose of this research study was to determine the relationship between teachers’ perceptions towards leadership capacity and organizational culture in the Marianists schools, India. The study was conducted to survey all the teachers from the selected 7 schools manage by the Marianists in India during the academic year 2016-2017. In this study, the research instrument for Part II investigated the teachers’ perception on leadership capacity was adapted from Pierce (2007) based on Lambert (2003) Leadership Capacity School Survey (LCSS) and questionnaire Part III measured the teachers’ perception for organizational culture adopted from Gruenert and Valentine’s (1998) School Culture Survey (SCS). The collected data from the survey re analyzed by Descriptive Statistics, Frequency and Percentage, Mean and Standard Deviation and Pearson Product Moment Correlation Coefficient. The study results showed that there was significant relationship between teachers’ perceptions towards leadership capacity and organizational culture. In order for the school improvement and sustenance, teachers and administrators from 7 Marianists schools in India are recommended to find out ways to create more opportunities for the teachers for sharing ideas, having frequent discussion, help each other in making lesion plans and collaboration in preparing school vision and mission to improve leadership capacity and organizational culture in their schools. Teachers should also pay attention on students’ achievement by giving more attention to each student.